Posting about politics: Media as resources for political expression on Facebook. Issue 2 (2nd April 2016) - Edgerly, Stephanie; Thorson, Kjerstin; Bighash, Leila; Hannah, Mark
ABSTRACT: This paper explores political expression on Facebook during the 2012 presidential debates. We investigate how individuals and organizations appropriated media resources to craft responses to the debates, and what this reveals about sources of influence in political communication on social media. In particular, we compare the stream of posts that spread widely during the debates—content that "went viral"—with more mundane practices of personal expression to show differences between the viral content that caught the attention of news media coverage about the debates and the posting practices of individuals using their Facebook as a site for individual expression.